The influence of grit on nurse job satisfaction: Mediating effects of perceived stress and moderating effects of optimism - Yang, Cui; Yang, Lu; Wu, Dongmei (Frontiers in Psychology, 2023)
Introduction Nurse job satisfaction, defined as the positive emotional state experienced by nurses regarding their profession, factors related to job performance and outcomes, can affect their career planning and development. Grit, defined as an individual’s relentless effort and enduring enthusiasm for long-term goals, is essential for developing nurses’ competence, increasing job satisfaction, and reducing the willingness to leave the profession. The present study aims to explore the correlation between grit and job satisfaction, whether perceived stress could act as a mediator of the relationship and whether optimism moderated the mediating effect among nurses working in hospitals in southwest China. Methods The cross-sectional study utilized self-reported data gathered from 709 nurses in southwest China. To analyze mediating and moderating effects, bootstrapping regressions were conducted. Results Perceived pressure mediated the relationship between grit and job satisfaction (indirect effect = 0.195, 95%CI [0.145,0.250]). Furthermore, moderated mediated analysis revealed that optimism moderated grit’s impact on perceived stress (moderating effect = 0.036, 95% CI [0.010, 0.061]). Discussion Low levels of grit might reduce nurses’ job satisfaction as their perceived stress levels increase. However, optimism among nurses could diminish this negative effect. Nursing managers should actively seek to improve the grit and optimism of hospital nurses while reducing their perceived pressure, thereby improving job satisfaction.